COMPARATIVE ASSESSMENT OF SPORTS ACTIVITY IN REAL AND VIRTUAL SPACE - Karvounis, Yu.A.; Karvounis, N.A.; Kapilevich, L.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to conduct a comparative assessment of the sports activities of kart drivers in real and virtual space. Methods and structure of the study. In total, 40 athletes took part in the experiment - 20 of them are e-sportsmen and 20 athletes of the technical type - the traditional motorsport direction "karting". At the first stage, a survey and additional interviews of the project participants were conducted to identify the motivation to engage in this sport, the features of the organization of the training process and the structure of recreational time, the assessment of eating behavior and self-awareness. At the second stage, an experiment was simulated, which consisted in the mutual exchange of types of training: karting drivers performed a training exercise in virtual reality, and cybersportsmen on a real circuit. Results and conclusions. A certain similarity of e-sports with other technical sports is shown. The priority elements in these areas are the formation of psychological stability, the development of technical skills, hand-eye coordination and speed. In cybersports, developments in the organization of physical training from technical sports can be effectively used. In turn, in motor sports, some elements of cybersports can also be applied to increase the effectiveness of the training process.